Effect of Natural Aging and Fatigue Crack Propagation Rate on Welded and Non-Welded Aluminum Alloy (AA2219˗T87) - Hassan Elahi (Advances in Science and Technology Research Journal, 2019)
Aluminum alloys are widely used for fabrication of aircraft, civil structures, and space vehicles. Fatigue life consideration of a material is the most important design criteria in many such critical applications. In this research work, a widely used Aluminum alloy AA2219-T87 was TIG welded using AA2319 as a filler material. The effect of natural aging on Fatigue Crack Propagation Rate (FCPR) of welded and non-welded compact tension (CT) specimens (AA2219˗T87) is studied. The relationship between stress intensity factor (∆K) and crack ratio (a/W) for different value of the crack length in base metal and the welded zone is presented. Paris curves for both welded and non-welded specimens and compared to study the effect of natural aging (NA) on FCGR and compared with non-aged specimens. The results obtained provide a base for the development of Structural Health Monitoring systems for the propagation of crack growth in such components.